The attitude of the Imāmī-Shīʿīs to the Companions of the Prophet - Kohlberg, E; Kohlberg, Etan (1972)
﻿ It is a commonly held view among non-Shī'īs that the Imāmī-Shī'ī attitude towards the Companions of the Prophet is characterised by hatred and contempt. In fact f the picture is far more complex and diverse. There are certain basic beliefs which are common to all Imāmī-Shī'īs, such as the belief that 'Alī b. Abī Ṭālib was the only rightful successor to Muḥammad. But in their attitude to individual Companions, as well as to the Ṣaḥāba as a whole, there are considerable differences between scholars of various periods, schools and geographic centres, and also between official Imāmī theology and popular Shī'ism. The aim of the present study is to examine the Imāmī-Shī'ī attitude to the Companions from two complementary angles: first, the Imāmī view of the Companions as Muslims; secondly, the Imāmī view of the Companions as authorities. The first point is directly connected with the Imāmī interpretation of events in the early period of Islam; the second involves doctrinal considerations which spring out of the Imāmī belief in an Imam in whom all authority is vested. Imāmī statements on most subjects have to be placed in the context of polemics against the Sunna. This is especially true for the Imāmī attitude to the Companions, since this is a subject about which both Sunnīs and Shī'īs held strong, often contradictory, views. In the present study, therefore, the investigation of Imāmī views is preceded by a chapter which examines Sunnī attitudes to the Ṣaḥāba. This chapter is followed by a discussion of Mu'tazilī views on the Companions, so that these views may be compared and contrasted with the official Imāmī attitude. The third chapter examines the doctrinal questions involved in the Imāmī attitude toward the Ṣaḥāba; it is followed by two chapters dealing with the Imāmī view of the rejected and the accepted Companions, respectively. In the the sixth and last chapter it is attempted to show that although Imāmī-Shī'īs regard the Imam as the supreme authority after the Prophet, the Companions are not entirely devoid of authority. The first appendix deals with biographies of some of the better known among the accepted Companions ; in the second appendix the main views of the Zaydiyya on the subject of the Ṣaḥāba are summarised.